Case reportAnaphylaxis after accidental ingestion of kiwi fruit - Gawrońska-Ukleja, Ewa; Różalska, Anna; Ukleja-Sokołowska, Natalia; Żbikowska-Gotz, Magdalena; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Numerous cases of anaphylaxis after ingestion of kiwi fruit, after the skin tests and during oral immunotherapy were described. The article describes the case of severe anaphylactic reaction that occurred in a 55-year-old patient after accidental ingestion of kiwi. Allergy to kiwi fruit was confirmed by a native test with fresh kiwi fruit. After the test, the patient experienced generalized organ response in the form of headache, general weakness and rashes on the neck and breast, and dyspnea. The patient had significantly elevated levels of total IgE and IgE specific to kiwi fruit.